PEMBERDAYAAN UKM MELALUI PENYULUHAN PENETAPAN HARGA JUAL PRODUK - Aprih Santoso; Ardiani Ika Sulistyawati; Nir Setyo Wahdi (Universitas YPPI Rembang, 2021)
The target audience for this community service is UKM players in Pedurungan Tengah Village. The main problem for SMEs in Pedurungan Tengah Village is that they have never set the selling price of the productcorrectly and are still carelessly an at will. The purpose of community service is to provide knowledge and understanding to UKM of Central Pedurungn Village in determining the selling price of products correctly. The implementation of this community service uses the method of counseling and simulations on determining the selling price of UKM products correctly. This community service can increase knowledge about the selling price of products by SMEs in Pedurungan Tengah Village in their business activities so that they can know the financial condition in the form of the actual amount of business profit on the correct product selling price.Keywords: Price, SMEs, Product, Sale, Profit